Adolescent Vision Health During the Outbreak of COVID-19: Association Between Digital Screen Use and Myopia Progression - Liu, Ji; Li, Baihuiyu; Sun, Yan; Chen, Qiaoyi; Dang, Jingxia (Frontiers in Pediatrics, 2021)
The coronavirus (COVID-19) pandemic has impacted education systems globally, making digital devices common arrangements for adolescent learning. However, vision consequences of such behavioral changes are not well-understood. This study investigates the association between duration of daily digital screen engagement and myopic progression among 3,831 Chinese adolescents during the COVID-19 pandemic. Study subjects report an average of 2.70 (SD = 1.77), 3.88 (SD = 2.23), 3.58 (SD = 2.30), and 3.42 (SD = 2.49) hours of television, computer, and smartphone for digital learning use at home, respectively. Researchers analyzed the association between digital screen use and myopic symptoms using statistical tools, and find that every 1 h increase in daily digital screen use is associated with 1.26 OR [Odds Ratio] (95% CI [Confidence Interval: 1.21–1.31, p < 0.001]) higher risks of myopic progression. Using computers (OR = 1.813, 95% CI = 1.05–3.12, p = 0.032) and using smartphones (OR = 2.02, 95% CI = 1.19–3.43, p = 0.009) are shown to be associated with higher risks of myopic progression than television use. Results from additional sensitivity tests that included inverse probability weights which accounted for heterogeneous user profile across different device type categories confirm that these findings are robust. In conclusion, this study finds that daily digital screen use is positively associated with prevalence of myopic progression and holds serious vision health implications for adolescents.